Prospective Single-Arm Study of Remifentanil-Propofol Anesthesia with Manual Right Hypochondrial Compression for Painless Gastroscopy in Obese Patients - Wang M; Tang J; Pan Z; Jiang H; Hu D; Zhu B; Liang Z; Zhao X; Li Y (Drug Design, Development and Therapy)
Mengxia Wang,1,* Jieke Tang,1,* Zhaojie Pan,2 Hongxue Jiang,1 Donghua Hu,1 Beibei Zhu,2 Zhaojia Liang,1 Xiangfeng Zhao,1 Yalan Li1 1Department of Anesthesiology, The First Affiliated Hospital of Jinan University, Guangzhou, Guangdong Province, People’s Republic of China; 2Department of Digestive Endoscopy Center, The First Affiliated Hospital of Jinan University, Guangzhou, Guangdong Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yalan Li, Department of Anesthesiology, The First Affiliated Hospital of Jinan University, No. 613, Huangpu West Avenue, Tianhe District, Guangzhou, Guangdong Province, 510630, People’s Republic of China, Email tyalan@jnu.edu.cnPurpose: The provision of comfortable and safe environment for painless gastroscopy in obese patients is an urgent clinical problem. This study aimed to determine the efficacy and safety of the novel Li anesthetic protocol for obesity (LAPO) which included remifentanil-propofol regimen, manual right hypochondrial compression (MRHC), easy-to-create mask, and jaw thrust at preoperative painless gastroscopy in obese patients.Patients and Methods: This prospective, single-center, single-arm trial recruited 106 participants underwent LAPO for gastroscopy. The primary outcome was the incidence of hypoxemia (peripheral oxygen saturation [SpO2]: 75% ≤ SpO2 < 90%, for > 10 s and ≤ 60 s). Second outcomes included severe hypoxemia, the lowest SpO2 (L-SpO2), duration of hypoxemia, and other events.Results: The 98 obese patients under LAPO, the median body mass index (BMI) was 39.2 kg/m2 and the incidence of hypoxemia was 27.5%, while the conventional anesthetic protocol for obesity (CAPO) in the reference was 40.4% with BMI 31.4 kg/m2. With the increase of class of obesity, a significant rise in the incidence of hypoxemia was observed, from class I by 11.8%, to 15.1% in class II, and 41.7% in class III. Paired t test showed that the L-SpO2 was significantly higher than L-SpO2 in overnight polysomnography (Nadir SpO2) (92% vs 76%, P< 0.001). Moreover, severe obstructive sleep apnea (OSA) was associated with a 4.019-fold higher risk of hypoxemia (Odds ratios [OR], 4.019; 95% confidence interval [CI], 1.184 to 14.610; P=0.028); diabetes was associated with a 4.790-fold higher risk of hypoxemia (OR, 4.790; 95% CI, 1.288 to 23.600; P=0.030).Conclusion: Compared with CAPO, LAPO reduced the incidence of hypoxemia from 40.4% to 27.5%, so, LAPO was safe and effective for painless gastroscopy. The finding might provide some new schedules for anesthetic management in the absence of advanced airway support instruments.Clinical Trial Registration: ChiCTR2300077889.Plain Language Summary: With the advancement of comfortable-oriented medication, gastroscopy is mostly performed under sedation and anesthesia. However, for obesity, there are changes in airway anatomy structure such as short neck, round chin, and large tongue, which makes them prone to airway obstruction after sleep or anesthesia, blocking the passage of oxygen in and out, which will cause hypoxemia over time and further cause damage to the body. Therefore, it is necessary to explore a safe and effective anesthesia management for painless gastroscopy in obesity. Our team’s work demonstrates that the novel Li anesthetic protocol (strategic anesthesia management of remifentanil combined with propofol and effective respiratory support through MRHC and jaw thrust, increased oxygen reserve via a novel mask) for obesity for painless gastroscopy with lacking advanced airway management devices is safe and efficient. Furthermore, our findings contribute to the understanding of the lowest SpO2 values that obese patients can tolerate during such procedures, establishing Nadir SpO2 as the cut-off point. We also identified severe OSA and diabetes as independent predictive risk factors for hypoxemia. If these findings are supported by further research, LAPO could aid anesthesiologists in developing specific anesthesia protocols and managing the risk of hypoxemia during painless gastroscopy for obese patients. Ultimately, this could expand access to comfortable and safe medical treatment for a broader spectrum of patients with obesity.Keywords: compression, hypoxemia, obese patient, obstructive sleep apnea, painless gastroscopy, propofol, remifentanil